2023
DOI: 10.1056/nejmoa2214172
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Craniectomy versus Craniotomy for Acute Subdural Hematoma

Abstract: The proofs will contain queries from the manuscript editor, as well as any queries that may be present in this file. The proof stage will be your next opportunity to make changes; in the meantime, please do not make any changes or send any new material to us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…Consequently, they were assessed for eligibility and full-text screening, which led to the inclusion of 17 studies. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The searching and screening process is shown in the flowchart ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, they were assessed for eligibility and full-text screening, which led to the inclusion of 17 studies. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The searching and screening process is shown in the flowchart ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hutchinson et al [ 27 ] conducted a randomized clinical trial and investigated the disability and quality of life with the EuroQol Group 5-Dimension 5-Level questionnaire (EQ-5D-5L). The EQ-5D-5L scores at 12 months were comparable between the DC and craniotomy groups.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the CT findings, prompt surgical evacuation of mass lesions or a primary decompressive craniectomy (DC) may be needed (e.g., see Fig. 1) [29 ▪▪ ]. A CT-angiogram should be performed in suspicion of traumatic cerebrovascular injuries such as skull base fractures involving the carotid canal [15].…”
Section: Emergency Department Managementmentioning
confidence: 99%
“…The Randomised Evaluation of Surgery with Craniectomy for patients Undergoing Evacuation of Acute SubDural Haematoma (RESCUE-ASDH) trial comparing DC versus craniotomy showed that patients with traumatic ASDH who underwent craniotomy or primary DC (as a primary operation), disability and quality-of-life outcomes were similar with the two approaches with no added benefit of performing DC [29 ▪▪ ].…”
Section: Surgical Perspectivesmentioning
confidence: 99%